Digital Locks, Physical Objects and Immaterial Works - Chapdelaine, Pascale (2017)
One of the greatest controversies in contemporary copyright law is the introduction of technological protection measures (TPMs) at the international and national level. By creating a separate parallel regime for digital copyright works, TPMs shifted the paradigm by redefining the rules of engagement of how users would increasingly access and experience digital copyright works.
Keywords: Pascale Chapdelaine